Screenwriting for Neurotics : A Beginner's Guide to Writing a Feature-Length Screenplay from Start to Finish - Sublett, Scott Winfield (Book collections on Project MUSE., 2014)
Screenwriting for Neurotics is a quirky and accessible handbook for beginning screenwriters. Whether you are a student in a screenwriting class or just someone who wants to try their hand at writing for film or television, this handy guidebook makes the entire process simple and unintimidating. Scott Winfield Sublett, a veteran screenwriter and screenwriting teacher, walks you step by step from start to finish and helps you navigate potential and unforeseen difficulties along the way, offering handy tips and suggestions to keep you from becoming blocked or stalled. Rather than throwing you into.